Dextran-5-(4-ethoxycarbonylphenylazo)salicylic acid ester, a polymeric colon-specific prodrug releasing 5-aminosalicylic acid and benzocaine, ameliorates TNBS-induced rat colitis. (27th May 2016) - Nam, Joon; Kim, Wooseong; Lee, Sunyoung; Jeong, Seongkeun; Yoo, Jin-Wook; Kim, Min-Soo; Jung, Yunjin
Abstract: Local anesthetics have beneficial effects on colitis. Dextran-5-(4-ethoxycarbonylphenylazo)salicylic acid ester (Dex-5-ESA), designed as a polymeric colon-specific prodrug liberating 5-ASA and benzocaine in the large intestine, was prepared and its therapeutic activity against colitis was evaluated using a TNBS-induced rat colitis model. Dex-5-ESA liberated 5-ASA and benzocaine in the cecal contents while (bio)chemically stable in the small intestinal contents and mucosa. Oral administration of Dex-5-ESA (equivalent to 10 mg 5-ASA/kg, twice a day) alleviated colonic injury and reduced MPO activity in the inflamed colon. In parallel, pro-inflammatory mediators, COX-2, iNOS and CINC-3, elevated by TNBS-induced colitis, were substantially diminished in the inflamed colon. Dex-5-ESA was much more effective for the treatment of colitis than 5-(4-ethoxycarbonylphenylazo)salicylic acid (5-ESA) that may not deliver benzocaine to the large intestine. Our data suggest that Dex-5-ESA is a polymeric colon-specific prodrug, liberating 5-ASA and benzocaine in the target site (large intestine), probably exerting anti-colitic effects by combined action of 5-ASA and benzocaine.